SOLUBLE EXPRESSION OF BACILLUS LICHENIFORMIS ATCC 27811 α-AMYLASE AND CHARACHTERIZATION OF PURIFIED RECOMBINANT ENZYME - A. Muazzam; 2; B. Malik; N. Rashid; S. Irshad; M. Fatima (Journal of Animal and Plant Sciences, 2019)
Alpha amylase (α-amylase) from Bacillus licheniformis shows great role in starch hydrolysis for industrial application due to its thermostability, long half-life and specificity. However, it is difficult to produce this enzyme in large quantities because of formation of inclusion bodies, but lowering the temperature to 18 °C leads to a soluble expression of protein. This also highlighted the efficacy of Escherichia coli as one of the best host for secretion of recombinant proteins. A further study to find an approach for a soluble expression of α-amylase was conducted here, using pET-22b(+)  as an expression vector and temperature optimization. Purified monomeric enzyme displayed a specific activity of 584.61 U/mg at 37 °C and a molecular mass of 52 kDa. Purification fold of recombinant α-amylase was 2.04 times in comparison to crude amylase extract.  Relative activity of enzymewas remarkably enhanced by Ca+2 but strongly impeded by Cu2+ and Na+1, highlighted the significance of Ca+2 as a cofactor for optimal amylase activity.
Keywords: Hydrolysis; Soluble; Thermostable; Industrial